Development of an Intervention for Improving Ingestion in Elders with Oropharyngeal Dysphagia. (28th July 2020) - Hansen, Tina; Thomassen, Julie Damm; Jensen, Lea Elm; Irgens, Maja Rosenkrands; Kjaersgaard, Annette
Abstract: Aim: To describe the development of a dysphagia management intervention for elders with sarcopenic oropharyngeal dysphagia (OD). Methods: The intervention development was guided by the UK Medical Research Council framework for developing and evaluating complex interventions. The steps included identification of the problem theory, the evidence base, the theory underpinning the intervention, the expected change mechanisms and a first draft of an intervention manual. This involved literature reviews and involvement of stakeholders, experts, and members of the target group. Results: A manualized client-centered and activity-based intervention that integrates functional resistance training of skills essential for a safe and efficient swallowing during ingestion of daily meals was developed for elders with sarcopenic OD. The intervention is informed by occupational therapy theory, self-determination theory, motor learning and affordance theory, and international standards for OD diets. Conclusion: The development steps resulted in a multicomponent intervention ready for feasibility testing before examining intervention efficacy.